Moving Ca2+ from the endoplasmic reticulum to mitochondria: is spatial intimacy enough?. (22nd May 2006) - Rutter, G.A.
Abstract : A number of studies in recent years have demonstrated that the ER (endoplasmic reticulum) makes intimate contacts with mitochondria, the latter organelles existing both as individual organelles and occasionally as a more extensive interconnected network. Demonstrations that mitochondria take up Ca 2+ more avidly upon its mobilization from the ER than when delivered to permeabilized cells as a buffered solution also indicate that a shielded conduit for Ca 2+ may exist between the two organelle types, perhaps comprising the inositol 1, 4, 5-trisphosphate receptor and mitochondrial outer membrane proteins including the VDAC (voltage-dependent anion channel). Although the existence of such intracellular ER–mitochondria 'synapses', or of an ER–mitochondria Ca 2+ 'translocon', is an exciting idea, more definitive experiments are needed to test this possibility.